Springer Handbook of Augmented Reality - Nee, Andrew Yeh Ching; Ong, Soh Khim. (Cham : Springer International Publishing : Imprint: Springer, 2023)
The Springer Handbook of Augmented Reality presents a comprehensive and authoritative guide to augmented reality (AR) technology, its numerous applications, and its intersection with emerging technologies. This book traces the history of AR from its early development, discussing the fundamentals of AR and its associated science. The handbook begins by presenting the development of AR over the last few years, mentioning the key pioneers and important milestones. It then moves to the fundamentals and principles of AR, such as photogrammetry, optics, motion and objects tracking, and marker-based and marker-less registration. The book discusses both software toolkits and techniques and hardware related to AR, before presenting the applications of AR. This includes both end-user applications like education and cultural heritage, and professional applications within engineering fields, medicine and architecture, amongst others. The book concludes with the convergence of AR with other emerging technologies, such as Industrial Internet of Things and Digital Twins. The handbook presents a comprehensive reference on AR technology from an academic, industrial and commercial perspective, making it an invaluable resource for audiences from a variety of backgrounds. .
Part I: Historical Developments -- Historical Developments and the Present State-of-the-Art -- Part II: Principles and Fundamentals -- AR Fundamentals and Associated Sciences -- Principles of Object Tracking and Mapping -- Part III: Software Toolkit and Techniques -- AR Software Development and Techniques -- Commercial AR Tools -- Part IV: Hardware and Peripherals -- Hardware and Peripherals -- Display Systems -- Tracking Systems -- Input Systems -- Part V: Application Areas -- Arts and Crafts -- Advertising -- Sports -- Tourism -- Education and Training -- Environment -- Fashion and Design -- Navigation and Guidance -- Architecture, Building and Archaeology -- Assistive Technologies and Rehabilitation -- Engineering and Science -- Logistics and Transportation -- Maintenance and Repair -- Medical and Surgery -- Military and Warfare -- Part VI: Content and Interface Development -- User Interface Development -- Part VII: Convergence with Emerging Technologies -- Internet of Things -- Industry 4.0, Digital Twin.
Keywords: Cooperating objects (Computer systems).; User interfaces (Computer systems).; Human-computer interaction; Business; Management science; Signal processing; Computer vision; Manufactures; Cyber-Physical Systems; User Interfaces and Human Computer Interaction; Business and Management; Digital and Analog Signal Processing; Computer Vision; Machines, Tools, Processes